Integrasi Kompos Kulit Kopi dan Biochar untuk Meningkatkan Kualitas Bibit Kopi Arabika - Sara, Dirga Sapta; Tridakusumah, Ahmad Choibar; Joy, Benny; Sofyan, Emma Trinurani; Suriadikusumah, Abraham (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
The application of organic amendments is an important strategy to improve seedling quality in coffee nurseries. This study aimed to evaluate the effects of coffee husk compost and biochar, appliedsingly and in combination, on the growth of Arabica coffee seedlings. The experiment was conductedin a nursery using polybags filled with 5 kg of growing media and arranged in a randomized completeblock design with seven treatments and four replications. The treatments consisted of a control, coffeehusk compost alone, biochar alone, and combinations of compost and biochar at different rates.Growth parameters observed included plant height, stem diameter, and number of leaves. The resultsindicated that all amended treatments significantly improved seedling growth compared to thecontrol. The best growth performance was consistently obtained from the combined application ofcoffee husk compost at 300 g polybag⁻¹ and biochar at 200 g polybag⁻¹, which produced the highestplant height, stem diameter, and leaf number. This treatment demonstrated a synergistic effectbetween coffee husk compost as a nutrient source and biochar as a soil conditioner that improved thegrowing media environment. These findings suggest that the combined use of coffee husk compost andbiochar at appropriate rates is an effective approach to enhance vegetative growth and overall qualityof Arabica coffee seedlings in nursery systems.